Virtues Of the King in Educational Administrators Affecting the Effectiveness of Schools Under Cluster 1 Of the Secondary Educational Service Area Office Nakhon Si Thammarat - Nootongkaew, Chontida (Journal of Dhamma for Life, 2025)
The purposes of this thesis were to 1) study the Ten Royal Virtues of school administrators under Cluster 1 of the Secondary Educational Service Area Office Nakhon Si Thammarat, 2) examine the effectiveness of schools under Cluster 1 of the Secondary Educational Service Area Nakhon Si Thammarat, 3) investigate the relationship between the Ten Royal Virtues of school administrators and the effectiveness of schools under Cluster 1 of the Secondary Educational Service Area Nakhon Si Thammarat and 4) identify the variables of the Ten Royal Virtues that can predict the effectiveness of schools under Cluster 1 of the Secondary Educational Service Area Nakhon Si Thammarat. The sample group was 260 teachers from schools under Cluster 1 of the Secondary Educational Service Area Nakhon Si Thammarat. The research instruments used were questionnaires. The statistical methods for data analysis included frequency, percentage, mean, standard deviation, Pearson’s correlation coefficient, and stepwise multiple regression. The findings were as follows: 1) The level of the Ten Royal Virtues of school administrators under Cluster 1 of the Secondary Educational Service Area Office Nakhon Si Thammarat showed a high average across all aspects. The virtues, ordered from the highest to the lowest average, are: Patience (Khanti), Absence of anger (Akkodha), Non obstruction (Avirodha), Self-control (Tapa), Morality (Sila), Uprightness (Ajjava), Non-violence (Avihimsa), Gentleness (Maddava), Generosity (Dana) and Philanthropy (Pariccaga) 2) The level of school effectiveness under Cluster 1 of the Secondary Educational Service Area Office Nakhon Si Thammarat showed a high average in all aspects. The aspects, ordered from the highest to the lowest average, were: students’ positive attitudes, problem-solving management by school administrators, school reform and development, and academic achievement 3.The relationship between Virtuse of the King of school administrators and school effectiveness under Cluster 1 of the Secondary Educational Service Area Office Nakhon Si Thammarat was found to be positively significant, with a relatively high level of correlation at the statistical significance level of .001 4.The predictive variables for the relationship between Virtues and school effectiveness under Cluster 1 of the Secondary Educational Service Area Office Nakhon Si Thammarat were identified as Avirodha, Sila, Khanti, and Maddava, which together predicted school effectiveness at 85.40%. The regression equations in raw scores and standard.